The Effects of the COVID-19 Pandemic on Unemployment Concerns among University Students - Canan Öykü Dönmez Kara; İlknur Karaaslan (Sosyal Siyaset Konferansları Dergisi)
The COVID-19 pandemic has affected the world since 2020, deepening economic and social problems. Worldwide, new investments have been suspended, restrictions have increased, and job opportunities have decreased, leading to negative impacts on employment rates. Although production and distribution have restarted in a limited and controlled manner to prevent economic and social collapse, the increasing trend in unemployment rates continues. In turn, increasing unemployment has increased the concerns of new university students looking for work after graduation. The aim of this study was to determine the effects of the COVID-19 pandemic on young adults’ concerns regarding entering the work force. The population of this study was senior students in the field of social sciences at the Çanakkale Onsekiz Mart University in Turkİye. The data were collected by a three-question survey, and content analysis was performed on the students’ responses. In total, 112 students participating in the study responded to the survey questions via Microsoft Teams, and their answers were transferred to Microsoft Office Word for analysis using the trial version of MAXQDA Analytics Pro 20. The research findings indicate that the COVID-19 pandemic has increased soon-to-be graduates’ anxiety related to finding a job; indeed, the concept of unemployment evoked negative thoughts in the minds of the participants. Social sciences students who will graduate soon were concerned about finding work before the pandemic and believed the COVID-19 pandemic had made it more difficult to participate in the workforce.